Інженерно-громадські об’єднання в промислово розвинених регіонах України як форма фахової комунікації: друга половина ХІХ - початок ХХ століття - Кушлакова, Н.М. (Історичний архів. Наукові студії, 2014)
Розглянуто різноманітні форми фахової комунікації спільноти вітчизняних інженерів
в другій половині ХІХ – на початку ХХ ст. Досліджено інженерно-громадські об’єднання
промислово розвинених регіонів України в означений період. Проаналізовано джерельну
базу (архівні матеріали) вивчення історії створення, відкриття та діяльності
інженерних громадсько-наукових товариств півдня Російської імперії. Рассмотрены различные формы профессиональной коммуникации сообщества
отечественных инженеров во второй половине XIX – начале ХХ в Исследованы
инженерно-общественные объединения промышленно развитых регионов Украины в
указанный период. Проанализирована источниковая база (архивные материалы)
изучения истории создания, открытия и деятельности инженерных общественно-
научных объединений юга Российской империи. Social political and technic economic changes in post-reform Russia contributed to the
formation and opening of various social scientific associations, whose purpose was primarily the
consolidation of scientific and technological forces and dissemination of scientific knowledge.
Fist of all the paper discusses various forms of professional communication community of
domestic engineers in the second half of XIX – early XX century. (societies, departments, clubs,
etc.) Engineering associations industrialized regions of Ukraine in the period are studied.
Analyzed Source base (archival material) of study of the history of creation, discovery and
engineering activities of social scientific societies in the south of Russian Empire
(Yekaterinoslav and Kharkiv department of Russian Technical Society, South Russian Society
of Technologists, Society of Petroleum Engineers who graduated from HEEC).